75 General paediatric nursing education at GOSH- new team, a new disease. (30th November 2020) - Akers, Elizabeth; Chavda, Sonia; Couzens, Chloe; Eccles, Louise; Grout, Sophie; Hart-Dyer, Kirsty; Law, Danielle; Painter, Amelia; Parker, Summer; Scott, Emma
Abstract : GOSH In response to the first wave of the Covid 19 pandemic, the profile of healthcare provision internationally underwent rapid and significant change. At GOSH, we opened several wards to support general paediatric care, enabling partner hospitals across the North Central London STP to increase their adult bed provision. This change in patient profile at GOSH presented many exciting opportunities. As educators, we supported the team to care for a wide variety of patients typically seen in general paediatrics; those with chest infections, diabetes, neonatal jaundice to safeguarding and mental health concerns. We could not have foreseen that a new and complex disease process would emerge. Covid-19 was expected, PIMS-TS brought new challenges; the nursing education needed to meet this challenge. The education strategy utilised a consistent and systematic approach; putting theory into practice and sharing emerging knowledge as it was identified. Nursing care had to adapt to continue to meet the changing needs of our patients and the teams caring for them. The nursing team formed to support General Paediatrics at GOSH were an amalgam of teams from across the Trust; primarily International Private Patients, Kingfisher Ward, Outpatients' and the Clinical Research Facility. The risks posed by merging new teams in a new environment with a new specialism are significant. Recognition of the heightened risks of this scenario drove our education strategy and planning. The strategy was one of hands on clinical support underwritten by regular multi-professional teaching. The General Paediatric Education Team was also an amalgam. This brought together a group of experienced educators, all with some background knowledge of general paediatrics. The challenges and risks of merging teams are always similar; this had to be factored into our rapidly formed education team; working effectively and safely whilst managing existing and new conditions and our own anxiety about Covid-19.